عقبات تطبيق نظام التكاليف على أساس الأنشطة Abcونظام التكاليف على أساس المواصفاتabciiفي المؤسسات الاقتصادية الجزائرية –دراسة عينة ميدانية لمجموعة من المؤسسات الاقتصادية في الجزائر- - خلايفة, ريحانة; بن خليفة, حمزة (جامعة الوادي - University of Eloued, 2022)
This study aims to demonstrate the scientific knowledge base for each of the Activity-Based (ABC) Costing and attribute-based costing system (ABCII), and to identify the most important obstacles that limit the application of these two systems in the environment of Algerian economic institutions. And 130 questionnaires subject to statistical study were retrieved, and the researchers reached a number of results, the most important of which is that Algerian economic institutions face difficulty in applying the costing system based on activities and the costing system instead of relying on the analytical information of the ABC system and the ABCII system that help them in the decision-making process.
Obstacles to application an activity-based costing ABC and attributes-based costing ABCII system in Algerian economic institution - A field sample study for a group of economic institutions in Algeria -
مقال
Keywords: محاسبة التكاليف ; نظام التكاليف على أساس الأنشطة ABC ; نظام التكاليف على أساس المواصفات ABCII ; المؤسسات الاقتصادية; Cost Accounting ; Activity Costing System ABC ; Attribute Based costing ABCII ; Economic Institutions